A report on factors related to the use of postpartum family planning and pattern of utilization among mothers in squatter settlements of Kathmandu Valley - Chhetri, Kamal Mahatara (Kamal Mahatara Chhetri, 2016)
The study was designed to establish "Factors related to the use of post partum family planning and pattern of utilization among mother in Squatter Settlements of Kathmandu Valley". The purposed study was provide information about utilization of postpartum family planning and to establish factors related to the use of postpartum family planning (PPFP) among mothers in Squatter Settlements of Kathmandu Valley. A community based cross sectional analytical study was conducted from December 2013 to February 2014. A cluster sampling technique was adopted .A total of 200 mothers, who had children completed one year & not exceeding three years in the study area was interviewed using a semi-structured and structured questionnaire that was combination of open and closed ended questions . The information was entered in excel and then was transferred and analyzed in SPSS version 20. The dependent variables were binary, while the independent variables were either dichotomous or categorical. Bivariate analysis (cross-tabulation, chi-squared tests) relationships between the independent variables and the dependent variables on utilization of postpartum family planning services was used for the analysis of data. The post partum family planning program had made substantial improvement in use of family planning methods, but still the progress is not worthy. So, an attempt was made to explore the factors related to use of post partum family planning. The results indicate that 69.2% of mothers had used post partum family planning at least once a time within one year of delivery. The results of this study revealed that occupation of husband, know about Post Partum Family Planning service, think cost of FP, husband agree to use of FP, were significantly associated with the use of post partum family planning.